Evaluating the Impact of Blockchain on Data Security and Transparency - Dr. Swati Patil; Ravi H Gedam; Dr. Sonal Patil (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The increasing reliance on digital systems for storing and managing data has raised significant concerns regarding data security and transparency. Traditional centralized systems often face challenges such as data breaches, unauthorized access, and a lack of accountability. Blockchain technology, with its decentralized nature and cryptographic features, presents a promising solution to address these issues. This paper evaluates the impact of blockchain on data security and transparency by analyzing its core features, such as immutability, consensus mechanisms, and encryption. Through case studies and comparative analysis, it is shown that blockchain enhances data security by providing tamper-proof records and strengthening access controls. Additionally, blockchain increases transparency by enabling traceability of transactions and offering verifiable audit trails. However, challenges remain, including scalability concerns and regulatory hurdles. The findings suggest that blockchain holds significant potential for improving data security and transparency, particularly in sectors like finance, healthcare, and supply chain management. Further research is needed to explore solutions to these challenges and to optimize blockchain’s effectiveness in real-world applications.